PENGARUH SIKAP, NORMA, DAN PERSEPSI KONTROL TENTANG PENYAKIT TIDAK MENULAR TERHADAP PERILAKU WARGA (Studi Pada Perilaku Terencana Anggota Posbindu di Kelurahan Ciparigi, Kecamatan Bogor Utara, Kota Bogor) - Mufida Nisa (2023)
Non-communicable diseases (PTM) are a serious problem worldwide because they cause 74% of deaths each year. The number of PTM cases has increased every year, including in Indonesia. This is triggered by various factors, one of which is the attitude and behavior of the community. The government created the Integrated Development Post (Posbindu) program to reduce the prevalence of PTM cases. This study aims to determine whether there is an influence of attitudes, norms, and perceptions of control on citizens' behavior in preventing the spread of PTM and to find out how big the influence is. The theory used is the theory of planned behavior. This research uses a quantitative approach with explanatory research. Data acquisition was carried out using a questionnaire and analyzed using multiple linear regression tests and T-tests to test the hypothesis. The results showed that attitudes had a significant effect on residents' behavior, this can be seen from the output of the regression analysis of 0.333, and t count 5.543 > t table 1.988. Norms have a significant effect on citizen behavior as seen from the results of the regression analysis output of 0.548, and t count 10.050 > t table 1.988. Perception of control has a significant effect on residents' behavior, this can be seen from the output of the regression analysis of 0.152, and t count 3.014 > t table 1.988. The conclusion of this study is that attitudes, norms, and perceptions of control influence the behavior of residents in preventing the spread of PTM so that the theory of planned behavior is true. Keywords: Attitudes, Norms, Perceived Control, Behavior, Non-Communicable Diseases, Posbindu.